Dynamic Correlations Between Gold, Oil, Bitcoin, and Global Equity Markets in the 2024–2026 Crisis Period: A Cross-Country Empirical Study - Mukhtar (PT Larva Wijaya Penerbit, 2026)
This study investigates the correlation dynamics among gold prices, crude oil prices, Bitcoin, and stock market indices of ten selected countries (USA, China, India, Germany, Japan, Saudi Arabia, Indonesia, Brazil, Vietnam, and Russia) over a 27-month period from January 1, 2024, to March 31, 2026—a condensed era marked by trade wars, oil shocks, geopolitical conflicts, and digital asset evolution. Using daily closing prices and Pearson correlation analysis, we examine six hypotheses grounded in modern portfolio theory, safe-haven theory, and macroeconomic spillover frameworks. Descriptive statistics reveal that Bitcoin exhibits the highest volatility, while gold shows moderate positive skewness, and stock indices display mixed distributional characteristics. Correlation results indicate that Bitcoin is most strongly correlated with the US stock market, followed by Brazil and Germany, supporting the integration hypothesis. Gold shows weak positive correlations with most stock indices, consistent with its role as a weak hedge. Oil exhibits near-zero or negative correlations with equities, particularly in oil-importing nations. The gold-oil correlation is positive but weak, while Bitcoin-gold and Bitcoin-oil are negligible, suggesting decoupling during crises. These findings provide crucial implications for portfolio diversification, risk management, and policy formulation in an era of compounded global shocks. Keywords:Gold, oil, Bitcoin, stock markets, safe haven.